Cancer with Pregnancy in a Cancer Hospital - Pariyar, J; Shrestha, B; Rauniyar, B P; Shrestha, J; Regmi, S C; jha, A K; Shrestha, S (Journal of Nepal Health Research Council, 2013)
Background: Cancer during pregnancy is rare, occurring one in every 1,000 pregnancies. Cancer itself rarely harms the baby and some cancer treatments are safe during pregnancy. However, treatment dilemmas often occur. Methods: Descriptive study was conducted at B. P. Koirala memorial cancer hospital. Case records of women with cancer and pregnancy from January 2001 to February 2012 were analyzed regarding their clinical details, treatment, follow-up and feto-maternal outcome. Results: Nineteen women, of 17 to 40 years had cancer with pregnancy. Observed cancers with pregnancy were: leukemia (4), head and neck (3), ovary (3), cervix (2), rectum (2), breast (1), Non-Hodgkin’s lymphoma (1), osteosarcoma (1), spinal cord (1) and vulva (1). Seven women (36%) presented in the second trimester and six women (32%) presented in the first and third trimester each. Seven (36%) women opted for termination of pregnancy for definitive treatment, five (26%) deferred treatment until delivery. Among the seven (36%) that accepted definitive treatment along with pregnancy, fetal demise occurred in three and delivery of healthy baby occurred in four. Nine babies born to mothers with cancer during pregnancy till date have normal growth and development. Total 10 (52%) of the mothers are in remission, six (32%) have died from disease. Conclusions: Cancers during pregnancy, more common in younger women, posed treatment challenges. Definitive cancer treatment could have greater fetal risk during the first trimester but could be offered with more acceptable risk in the second and third trimesters. Keywords: cancer; chemotherapy; pregnancy; radiotherapy.